Casebooks in Early Modern England:: Medicine, Astrology, and Written Records - Kassell, Lauren (Bull Hist Med, 2014)
Casebooks are the richest sources that we have for encounters between early modern medical practitioners and their patients. This article compares astrological and medical records across two centuries, focused on England, and charts developments in the ways in which practitioners kept records and reflected on their practices. Astrologers had a long history of working from particular moments, stellar configurations, and events to general rules. These practices required systematic notation. Physicians increasingly modeled themselves on Hippocrates, recording details of cases as the basis for reasoned expositions of the histories of disease. Medical records, as other scholars have demonstrated, shaped the production of medical knowledge. Instead, this article focuses on the nature of casebooks as artifacts of the medical encounter. It establishes that casebooks were serial records of practice, akin to diaries, testimonials, and registers; identifies extant English casebooks and the practices that led to their production and preservation; and concludes that the processes of writing, ordering, and preserving medical records are as important for understanding the medical encounter as the records themselves.